Orbis Pictus - Sulik, Martin; Strba, Martin; Nvotová, Dorota; Vasaryová, Emilie; Kovár, Frantisek (Magic Box, 2007)
A defiant misfit teenaged girl goes on a magical journey of self-discovery through a surrealistic enchanted forest after she is booted out of boarding school. Tereza goes through the beautiful countryside en route to Bratislava, the capital city where her estranged mother lives. Along the way, she has several quirky adventures, overcomes a number of obstacles and meets assorted weird characters, including a sad young man who is about to marry a woman old enough to be his mother, and an old woman who is buried up to her waist in order to relieve her pain. Matters don't get any less strange when she finally reaches her destination. [movies.nytimes.com]